Climate change assessment on flood occurrence in Kota Tinggi, Johor - Anuar, Nur Danisyah; Rahmat, Siti Nazahiyah (Penerbit UTHM, 2022)
Flood is associated with the climatic change where the climate variable has detrimental impact on hydrologic cycle. Johor is among the affected states by flood catastrophe for almost every year. Over the year, Johor has experienced increasing amount of rainfall. However, studies on future rainfall pattern in Johor are still quite limited. Thus, this study was carried out to identify climate change impacts by projecting rainfall data using Statistical Downscaling Model (SDSM) and predicting flood events utilizing the Standardised Precipitation Index (SPI). Through SDSM, the rainfall data was projected in corresponding with General Circulation Models (GCM) predictor under three different representative concentration pathway (RCP) of RCP2.6, RCP4.5 and RCP8.5 that consider different emission level in future. Future observation in the upcoming 30 years for both studied stations at Kota Tinggi, Johor recorded increasing trend in the projected mean annual rainfall under three scenarios where the highest change in projection was +12.2% under RCP8.5 at Ladang Telok Sengat station. From SPI analysis, it is predicted that there will be frequent occurrence of flooding in the upcoming 30 years due to more positive SPI values (> 1) indicated by the studied stations. From the study, the authorities can come up with better mitigation plan to supervise the flood event in the future.